Correlation Between Levels of C-Reactive Protein, D-Dimer, and Ferritin in Covid-19 Patients Infected with Different Bacterial Species - Aqeel Abbas KAREEM; Adnan Hamad AUBAID (Modern Medicine)
Introduction: The fast dissemination of SARS-CoV-2 occurred swiftly across Iraq and various nations globally, leading to a widespread viral pandemic. C-reactive protein, Ferritin, and Ddimer have emerged as pivotal molecules within the immune system, playing a central role in coordinating cellular defense mechanisms against inflammation. This study aimed to correlate the role of CRP, ferritin- and D-dimer parameters in patients of coronavirus disease - 2019 (COVID-19) associated bacterial co-infection. Methods: Sputum and blood samples were collected from patients who diagnosed a COVID-19 by an internal medicine specialist and positive PCR test. The collected samples of sputum were inoculated on selective culture media, the isolated colonies were further subjected to subculture and identified using cultural and biochemical tests. Antibiogram testing was performed with selected antibiotics. An automated VITEK-2 compact system using AST-N222 cards and - chroma11 TM D-Dimer kits was used to determine the levels or titers of these parameters using ELISA and fluorescence Immunoassay (FIA) for the quantitative determination in human whole blood/serum /plasma according to manufacturing instructions. Results: the results revealed a significant rise in ferritin levels among individuals with moderate and severe diseases in comparison to those with mild cases. Among severe patients, ferritin levels were significantly higher than in non-severe cases (P=0.02). The mean C-Reactive protein levels were 92.54±68.94, 97.66±65.70, and 123.83±65.80 in Covid19 patients infected with M. catarrhalis, P. aeruginosa, and K. pneumonia, respectively. The study showed levels of ferritin non-significant increase in patients infected with COVID-19 and K. pneumoniae when compared with other groups was none. Conclusion: In this study, the results proved the presence of an association between the elevated levels of tested biomarkers (CRP, Ferritin, D-dimer) in co-infection by bacteria of COVID-19 patients.